THEORETICAL ASSUMPTIONS TO THE DESIGN OF THE NATIONAL LOGISTICS SUPPORT SYSTEM - Chaberek, Mirosław; Mańkowski, Cezary (Journal of Positive Management, 2019)
Purpose: The purpose of this article is to formulate theoretical assumptions to the design of the national logistics support system at the model form according to the logistics needs of the national economy. Methodology: The methodology approach includes such methods as holism, modelling and logical reasoning, which are supported by such research tools as system, model, induction, reduction, deduction. Findings: The research results are presented at the macro-model of servicing the country recourses’ requirements by the national logistics system. The structure of the system is hierarchical, composed of three level and three logistics subsystems of macroeconomic model of the national economy, macro-model of the logistics service of the country economy, and operational model of logistics chains. Originality/value: The proposed set of theoretical assumptions formulated at the form of the national logistics support system model, fill the literature gap on macrologistics system on a country level.